PIGW‐related glycosylphosphatidylinositol deficiency: Description of a new patient and review of the literature. Issue 6 (21st March 2020) - Peron, Angela; Iascone, Maria; Salvatici, Elisabetta; Cavirani, Benedetta; Marchetti, Daniela; Corno, Silvia; Vignoli, Aglaia
Abstract: Inherited glycosylphosphatidylinositol (GPI) deficiencies are a group of clinically and genetically heterogeneous conditions belonging to the congenital disorders of glycosylation. PIGW is involved in GPI biosynthesis and modification, and biallelic pathogenic variants in this gene cause autosomal recessive GPI biosynthesis defect 11. Only five patients and two fetuses have been reported in the literature thus far. Here we describe a new patient with a novel homozygous missense variant in PIGW, who presented with hypotonia, severe intellectual disability, early‐onset epileptic seizures, brain abnormalities, nystagmus, hand stereotypies, recurrent respiratory infections, distinctive facial features, and hyperphosphatasia. Our report expands the phenotype of GPI biosynthesis defect 11 to include stereotypies and recurrent respiratory infections. A detailed and long‐term analysis of the electroclinical characteristics and review of the literature suggest that early‐onset epileptic seizures are a key manifestation of GPI biosynthesis defect 11. West syndrome and focal‐onset epileptic seizures are the most common seizure types, and the fronto‐temporal regions may be the most frequently involved areas in these patients.